The use of the iStar Framework for modeling tax compliance programs - Speck, Jefferson Rodrigo; Andrade, Sidgley Camargo de; Santander, Victor Francisco Araya; Sorbar, Fabiane (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2026.42434, 2026)
Modeling tax compliance programs is essential for organizations because these programs translate statutory obligations into organizational controls throughout the tax reporting lifecycle, requiring coordinated responsibilities, evidence generation, and data consistency across departments and thirdparty systems. Although traditional early requirements and process models are commonly used to model tax compliance programs, they are limited in capturing key dependencies among entities such as departments and outsourced systems. To address this gap, this study uses the iStar 2.0 framework as an alternative model to capture these dependencies. This framework focuses on representing actors, goals, and dependencies rather than processes. A proof of concept was conducted in a real-world scenario, where requirements were gathered through interviews and questionnaires and validated using the Delphi technique. The empirical results demonstrate the viability of the iStar framework for modeling and enriching tax compliance programs, highlighting responsibilities and quality attributes such as traceability and auditability. Therefore, the iStar 2.0 framework can be considered for modeling and enriching compliance programs.